On the importance of household production in collective models: Evidence from U.S. data - Olivier Donni; Eleonora Matteazzi (Institute for the Study of Labor (IZA), 2010)
The present paper develops a theoretical model of labor supply with domestic production. It is shown that the structural components of the model can be identified without a distribution factor, thereby generalizing the initial results of Apps and Rees (1997) and Chiappori (1997). The theoretical model is then estimated using the ATUS data. The empirical results are compared to those obtained from a similar model without domestic production.
Keywords: D13; J21; J22; 330; Collective model; market labor supply; domestic labor supply; household production; identification; ATUS; Haushaltsökonomik; Arbeitsangebot; Haushaltsproduktion; Zeitbudgetforschung; USA